Centre-state relations - Lessons and prospects (Note) - Mathur, Krishna Mohan (2001)
In a federal country of sub-continental dimensions like India, the lessons from Centre-state relations must be learnt on a continuous basis from the past experience. Here is an analysis and critical evaluation of these experiences in the context of the new era of coalition politics. - Reproduced
Keywords: Note; Federal state relations